Quelques théorèmes sur les séries de Dirichlet - Tourpanova, V. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. М. Турпанова. Некоторые теоремы о рядах ДирихлеV. Turpanova. Kai kurios teoremos Dirichle eilučių klausimu